Perceptions of Powerlessness Are Negatively Associated with Taking Action on Climate Change: A Preregistered Replication - Williams MN; Jaftha BA (Mary Ann Liebert, Inc)
Despite segments of skepticism, the majority of the general public in most countries believe that climate change is occurring and caused by human activities. Behavior changes by individuals can reduce greenhouse gas emissions to at least some extent, but a range of psychological and economic barriers can prevent individuals from taking action. A survey of New Zealanders by Aitken, Chapman, and McClure (2011) reported that belief in human influence on climate change and the risks of climate change were positively correlated with taking action on climate change. Conversely, perceptions of powerlessness and the commons dilemma were negatively correlated with taking action on climate change. Feeling powerless was associated with placing less importance on climate change as an influence on actions. Although the study by Aitken et al. has been influential, it was exploratory in nature, had a moderate sample size, was not preregistered, and has not previously been replicated. In this study, we report a preregistered replication with a sample of 352 Australians testing four hypotheses based on Aitken et al.'s findings (as summarized above). All four hypotheses were supported, reproducing Aitken et al.'s key findings
“Final publication is available from Mary Ann Liebert, Inc., publishers https://www.liebertpub.com/doi/10.1089/eco.2020.0012]”
Keywords: Climate change; Powerlessness; Commons dilemma; Behavior change; Ecopsychology; Conservation psychology; 1117 Public Health and Health Services; 1701 Psychology